Gridded, high-resolution ocean observatories initiative profiler data from the Washington continental slope, 2014–2025Zenodo - Craig M. Risien; Russell A. Desiderio; Jonathan P. Fram; Edward P. Dever (Data in Brief, 2025)
The NSF Ocean Observatories Initiative (OOI) Coastal Endurance Washington Offshore Profiler Mooring (CE09OSPM) was first deployed in April 2014. The mooring is located on the Washington continental slope about 60 km west of Grays Harbor, WA at 46.8517°N, 124.982°W. This mooring includes a McLane® Moored Profiler (MMP), which carries energy-efficient instruments that simultaneously measure water temperature, conductivity, pressure, and dissolved oxygen, as well as photosynthetically active radiation, chlorophyll-a fluorescence, coloured dissolved organic matter, optical backscatter, and water velocity. Moving at about 25 cm/s, the MMP collects up to eight profiles per day between approximately 35 m and 510 m water depth. This data article describes a data set that consists of 3244 daily averaged temperature, practical salinity, potential density, and dissolved oxygen profiles collected between October 2014 and May 2025 that were processed using a MATLAB® toolbox that was specifically created to process OOI MMP data. The toolbox imports unpacked MMP data files, applies the necessary calibration coefficients and data corrections, including adjusting for thermal-lag, flow, and sensor time constant effects, and produces a final, 0.5-dbar binned data set. From the daily, gridded profiler data, we calculated seasonal cycles for each variable using a least squares fit of the annual, semi-annual, and triannual harmonics. These gridded profiler data, which are vital for advancing our understanding of subsurface oceanographic phenomena — including modulation of the California Undercurrent, water mass and upwelling source water variability, marine heat waves, ocean acidification, and the increasing prevalence and severity of seasonal hypoxia in the Northern California Upwelling System — are available via Zenodo at https://doi.org/10.5281/zenodo.15627742.